2015
DOI: 10.1007/s10578-015-0608-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Seclusion and Restraint in a Pediatric Psychiatry Day Hospital

Abstract: The use of seclusion and restraints (SR) in acute hospital settings remains a controversial practice. Despite the focus on SR in the psychiatric services literature, data on SR use in pediatric day hospital settings is lacking. A case-control retrospective analysis for children admitted into a pediatric psychiatry day hospital in a 2-year span examined predictors of SR use. Demographic and clinical descriptors were examined in relation to SR events using univariate and multivariate regression models. Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
2
11
0
2
Order By: Relevance
“…Controlling for factors such as aggression, psychotic disorders, and anxiety disorders have been uniquely associated with greater use of seclusion (Duke et al, 2014; Dumais et al, 2011; Gullick et al, 2005; Timbo et al, 2016). But, contrary to our hypotheses, these disorders were not significantly associated with seclusion in univariate analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Controlling for factors such as aggression, psychotic disorders, and anxiety disorders have been uniquely associated with greater use of seclusion (Duke et al, 2014; Dumais et al, 2011; Gullick et al, 2005; Timbo et al, 2016). But, contrary to our hypotheses, these disorders were not significantly associated with seclusion in univariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, we provided novel information regarding the use of seclusion in an adolescent unit, particularly through the investigation of nurse factors on adolescent units and determining the relative contribution of both inpatient and nurse factors to seclusion outcomes. Previous single‐site studies have also given valuable insights into seclusion (Duke et al, 2014; Muir‐Cochrane et al, 2014; Timbo et al, 2016; Vidal et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study from Iowa (2011), 70% of the adult inpatients who experienced the most instances of seclusions or restraints had experienced childhood abuse [18]. Another study found that children with post-traumatic stress disorder (PTSD) and/or a history of physical abuse had a significantly higher risk of being secluded or restrained in a U.S. pediatric day hospital [19].…”
Section: Introductionmentioning
confidence: 99%
“…The baseline rates of seclusions were 26% of patients or 67 per 1000 patient days, and the baseline rates of restraints were 29% of patients or 42.7 per 1000 patient days. Recent studies on child and adolescent psychiatric inpatient units reported rates of restraint between 6.5 and 29% of admitted patients; 6.5% restraint, Norway [25,26], 12% restraint or seclusion, the U.S. [19], 26.9% restraint or seclusion, Australia [27], 29% restraint or seclusion, the U.S. [28], 16.9% restraint or seclusion, the U.S. [29], 6.9% mechanical restraint only, Finland [30]. A review by Beghi et al (2013) reported a 3.8-20% prevalence of restraint utilization in adult psychiatric units [31].…”
Section: Introductionmentioning
confidence: 99%